Economic value of Bandung Orchid Forest, West Java - Fikri Nugroho Utomo; Dika Supyandi; Nur Syamsiyah; Ernah Ernah (Center for Science and Technology, IAIN Surakarta, 2020)
Indonesia has various tourist attractions. Agro-tourism is one of the potential tourism. Orchid Forest is an agro-tourism object that combines pine forest areas with orchid cultivation. Tourist attractions that utilize the potential of natural resources have an unknown economic value. This research aims to know the economic value of Orchid Forest and what factors influence the frequency of visits. This research used an individual travel cost method (ITCM) to estimate the economic value of Orchid Forest. The results indicate factors that significantly influence the frequency of visits are respondents' age and residence distance. The value of consumer surplus is Rp 102,000 and the economic value of Orchid Forest in 2019 was Rp 70,365,618,000. This value will give a new perspective for public authorities for the protection and further development of tourist attractions in the future.